A systematic review and meta-analysis of the effect of photodynamic therapy for the treatment of oral mucositis - de Oliveira, Analú Barros [UNESP]; Ferrisse, Túlio Morandin [UNESP]; Basso, Fernanda Gonçalves; Fontana, Carla Raquel [UNESP]; Giro, Elisa Maria Aparecida [UNESP]; Brighenti, Fernanda Lourenção [UNESP] (Elsevier, 2021)
Background: Oral mucositis is a significant reaction to antineoplastic treatment characterized with pain, nutritional compromise, impact on the quality of life, interruption in cancer therapy and risk for infection. There is no effective standard protocol for the treatment of oral mucositis. This study aims to synthesize the scientific evidence available about the effects of photodynamic therapy on treatment of oral mucositis. Methods: PubMed, Scopus, Web of Science, Science Direct, Scielo, Embase and Cochrane libraries were searched. Two independent and calibrated researchers (kappa = 0.92) performed all systematic steps according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). To access the risk of bias, RoB 2 and Delphi list criteria for clinical trials were used. Meta-analysis was conducted using the R software with “META” package. Results: Clinical and randomized clinical trials were included with a total of five articles. Meta-analysis, level of evidence, and risk of bias assessment were performed showing that photodynamic therapy was effective in reducing healing time in association with low-power laser therapy when compared to low-power laser therapy alone (p = 0.0005). Conclusion: Photodynamic therapy presents promising results for the treatment of oral mucositis. It may be an effective therapeutic option, contributing to the healing of injured tissues especially in the time needed for repair.
Keywords: Oral mucositis; Photodynamic therapy; Systematic review, meta-analysis review